2003
DOI: 10.1086/345917
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of the Progenitors of Gamma‐Ray Bursts

Abstract: The various possibilities for the origin ("progenitors") of gamma-ray bursts (GRBs) manifest in differing observable properties. Through deep spectroscopic and high-resolution imaging observations of some GRB hosts, I demonstrate that well-localized long-duration GRBs are connected with otherwise normal star-forming galaxies at moderate redshifts of order unity. Using high-mass binary stellar population synthesis models, I quantify the expected spatial extent around galaxies of coalescing neutron stars, one of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 223 publications
(492 reference statements)
0
7
0
Order By: Relevance
“…Unfortunately, a simple increase in the overall energy budget cannot by itself explain the deduced luminosity evolution. Frail et al (2001) and Bloom et al (2003) have recently shown observational evidence suggesting that the collimation corrected GRB energies E γ are actually narrowly cluster around the 10 51 ergs typical of SNe explosions. They come to this conclusion by correcting the observed prompt isotropic equivalent energy release E iso of several GRBs with known redshift by a factor of 1 − cos θ j , where θ j is the canonical jet opening angle.…”
Section: The Nature Of the Luminosity Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, a simple increase in the overall energy budget cannot by itself explain the deduced luminosity evolution. Frail et al (2001) and Bloom et al (2003) have recently shown observational evidence suggesting that the collimation corrected GRB energies E γ are actually narrowly cluster around the 10 51 ergs typical of SNe explosions. They come to this conclusion by correcting the observed prompt isotropic equivalent energy release E iso of several GRBs with known redshift by a factor of 1 − cos θ j , where θ j is the canonical jet opening angle.…”
Section: The Nature Of the Luminosity Evolutionmentioning
confidence: 99%
“…Furthermore, an observer viewing the GRB at a small θ v would see an extremely powerful burst, with the observed luminosity declining as some function of increasing θ v . A jet structure with a functional form of ǫ(θ) −2 is required to reproduce the observed t j ∝ E iso , i.e the Frail et al (2001) and Bloom et al (2003) results. If the requirement of a narrow E γ and L γ distribution is broken, then any power law structure θ k could still produce the observed steepening in the afterglow light curve.…”
Section: The Nature Of the Luminosity Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing set of observations seem to support this paradigm: long bursts appear to be concentrated near the peak emission in star-forming galaxies, are even more centrally located than supernovae [Vreeswijk et al, 2001, Bloom, 2003, Fruchter et al, 2006. Full confirmation of the accretion disk paradigm required observations demonstrating short GRBs arise from mergers, e.g.…”
Section: Distributions Of Disk Enginesmentioning
confidence: 99%
“…Observational and theoretical studies of the host galaxies of binary compact objects pre-date the detection of gravitational waves (e.g. Perna & Belczynski 2002;Voss & Tauris 2003;Bloom 2003;Fan et al 2005;Belczynski et al 2006;Covino et al 2006;Nakar et al 2006;O'Shaughnessy et al 2008;Piranomonte et al 2008;Guetta & Stella 2009;D'Avanzo et al 2009;Antonelli et al 2009;Berger 2010;Kopač et al 2012;Margutti et al 2012;Fong & Berger 2013;Fong et al 2015). Since the short gamma-ray bursts (SGRBs) have long been suspected to be associated with BNS and neutron star-black hole (NSBH) mergers, studies of the galaxy hosts have provided remarkable clues onto the evolutionary channels leading to the observed SGRBs.…”
Section: Introductionmentioning
confidence: 99%